A proposed cascade of vascular events leading to granulomatous amoebic encephalitis - Baig, Abdul Mannan; Khan, Naveed Ahmed * (Elsevier, 2015)
Granulomatous amoebic encephalitis due to Acanthamoeba is a chronic disease that almost always results in death. Hematogenous spread is a pre-requisite followed by amoebae invasion of the blood-brain barrier to enter the central nervous system. Given the systemic nature of this infection, a significant latent period of several months before the appearance of clinical manifestations is puzzling. Based on reported cases, here we propose pathogenetic mechanisms that explain the above described latency of the disease.